Students’ perceptions of the educational environment of medical internship in two medical schools in Fortaleza - Filho, Manoel Coutinho; Ribeiro, Lucas Loiola Ponte Albuquerque; Bessa, Olívia Andréa Alencar Costa (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Introduction: The educational environment is made of a web of interlinked factors which interact constantly with one another and influence the teaching and learning process. Studying the educational environment becomes essential for the development of modern and effective curricula. The Dundee Ready Education Environment Measure (DREEM) inventory is a validated global tool for quantifying the main factors involved in this process. The medical internship usually lasts two years, and it is critical for medical training. This study aims to evaluate the perception of the medical interns about the educational environment who are from two medical schools in Fortaleza, one of which uses an active learning methodology (A) and the other uses a traditional learning methodology (B). Method: This is an observational, crosssectional and quantitative study. Sampling involved students in medical internships from two medical schools. The instruments for collecting data were: a sociodemographic questionnaire with nine questions, and the DREEM questionnaire. The quantitative data were expressed as mean ± and standard deviation in accordance with the analysis of data distribution normality, which was made by using the Kolmogorov-Smirnov Normality Test and histograms. The Student T test was used in order to compare the DREEM score between two groups, and the one-way ANOVA followed by the Tukey’s post-test were used in cases of comparing three or more groups. Results: The DREEM global scores of the medical interns were 144,65 ± 26,21. Regarding the medical school with traditional learning methodology, the value found was 122.45 ±25.42, while in the medical school with active learning methodology the value was 154.75 ± 19.55. The analysis of item 25 of the questionnaire related to contents that require memorization pointed to a mean of 1.46±1.04, and it indicated a problematic area. The score of the dimension related to the Perception of Preceptors in the internship was 33.75± 6.18, with the teachers being considered as models. Conclusion: In the medical intern’s view which came from the medical school with traditional learning methodology, the classification showed “more positive scores than negatives”, while relating to those who came from medical school with active learning methodology, the perception points to “excellent”. The medical interns considered as a weak point the existence of some situations which they are subjected to the learning of memorable facts. The strong point is the perception of the preceptors by students.